RETRACTED: CuO and CeO2 Nanostructures Green Synthesized Using Olive Leaf Extract Inhibits the Growth of Highly Virulent Multidrug Resistant Bacteria - Maqbool, Qaisar; Nazar, Mudassar; Maqbool, Ayesha; Pervez, Muhammad T.; Jabeen, Nyla; Hussain, Talib; Franklin, Gregory (Frontiers in Pharmacology, 2018)
One of the major challenges of nano-biotechnology is to engineer potent antimicrobial nanostructures (NS) with high biocompatibility. Keeping this in view, we have performed aqueous olive leaf extract mediated one pot facile synthesis of CuO-NS and CeO2-NS. Prepared NS were homogenous, less than 26 nm in size, and smaller crystallite units as revealed by SEM and XRD. FTIR analysis of CuO-NS and CeO2-NS showed typical Cu-O prints around 592-660 cm-1 and Ce-O bond vibrations at 453 cm-1. The successful capping of CuO-NS and CeO2-NS by compounds present in the plant extract was further validated by High Performance Liquid Chromatography (HPLC) and Thermal-Gravimetric Analysis (TGA). Active phyto-chemicals from the leaf extract simultaneously acted as strong reducing as well as capping agent in the NS synthesis. NS engineered in the present study showed antibacterial activities against highly virulent multidrug-resistant gram-negative bacterial strains (E. coli, E. cloacae, A. baumanni and P. aeruginosa), alarmed by World Health Organization (WHO) at extremely low dosage. Furthermore, CuO-NS and CeO2-NS did not show any cytotoxicity on HEK-293 cell lines indicating that the NS green synthesized in the present study are biocompatible.